Heat-treated human platelet pellet lysate modulates microglia activation, favors wound healing and promotes neuronal differentiation in vitro. (17th February 2021) - Nebie, Ouada; Barro, Lassina; Wu, Yu-Wen; Knutson, Folke; Buée, Luc; Devos, David; Peng, Chih-Wei; Blum, David; Burnouf, Thierry
Abstract: The neurorestorative efficacy of human platelet lysates in neurodegenerative disorders is still under investigation. Platelets prepared from standard and pathogen reduced platelet concentrates were pelletized, washed, concentrated, and subjected to freeze-thawing. The lysate was heated to 56°C for 30 min and characterized. Toxicity was evaluated using SH-SY5Y neuroblastoma, BV-2 microglial, and EA-hy926 endothelial cells. Inflammatory activity was tested by examining tumor necrosis factor (TNF) and cyclooxygenase (COX)-2 expressions by BV-2 microglia with or without stimulation by lipopolysaccharides (LPS). The capacity to stimulate wound healing was evaluated by a scratch assay, and the capacity to differentiate SH-SY5Y into neurons was also examined. Platelet lysates contained a range of neurotrophins. They were not toxic to SH-SY5Y, EA-hy926, or BV-2 cells, did not induce the expression of TNF or COX-2 inflammatory markers by BV-2 microglia, and decreased inflammation after LPS stimulation. They stimulated the wound closure in the scratch assay and induced SH-SY5Y differentiation as revealed by the increased length of neurites as well as β3-tubulin and neurofilament staining. These data confirm the therapeutic potential of platelet lysates in the treatment of disorders of the central nervous system and support further evaluation as novel neurorestorative biotherapy in preclinical models.